Study on Income Effect of Nutrient Intake Structure of Migrant Workers: The Case of China - Zhi-peng HE; Kang YU (International Journal of Engineering and Management Research, 2020)
This paper empirically analyzes the income effect of the nutrient intake structure of migrant workers based on the 2014 survey data on the employment and food demand of urban migrant workers in China. The results showed that after controlling for factors such as labor intensity, height and weight, the monthly average income significantly increased the calorie intake of migrant workers, and the income elasticity was 0.052. From the perspective of nutrient intake structure, the average monthly income had no significant effect on the carbohydrate intake of migrant workers, but significantly increased the fat and protein intake of migrant workers, and the income elasticity was 0.222 and 0.075, respectively. Nutrition has not linear relationship between demand and income. The effect of average income on caloric intake of migrant workers in low income group, middle income group and high income group decreases with the increase of income group, until it has no significant effect on high income group, and heat demand income elasticity of low-income as well as middle-income group of migrant workers was 0.182 and 0.092, respectively.